The rise of bots: exploring Malaysians' intention to use chatbots for travel planning / Nur Alissya Nazri, Faiz Izwan Anuar and M Zainul Ridho - Nazri, Nur Alissya; Anuar, Faiz Izwan; Ridho, M Zainul (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Chatbots is a game changer in the travel industry. With enhanced functionality, chatbots emerge as an innovative technology designed to expedite the travel planning process. However, their successful integration into the Malaysian tourism industry is contingent on factors such as perceived ease of use, perceived usefulness, and, most importantly, trust. Thus, by extending the Technology Acceptance Model (TAM) to include trust as a vital construct, this research seeks to understand how perceived ease of use, perceived usefulness, and trust impact users' behavioral intention to use chatbot technology for travel planning. Using a quantitative approach, the study is expected to be dispersed via an online survey to gather data from Malaysian adults familiar with chatbots. The findings shall have practical implications for the tourism industry, chatbot developers, and businesses aiming to optimize chatbot services for enhanced travel experiences, thus contributing to the evolving landscape of technology adoption in Malaysia's tourism sector.